NEW RECORDS OF GENUS PTECTICUS LOEW, 1855 (DIPTERA: STRATIOMYIDAE) FROM PAKISTAN - M. A. Hassan; I. Bodlah; M. F. Malik; A. Gull-E-Fareen (Journal of Animal and Plant Sciences, 2019)
The species of genus Ptecticus Loew, 1855 are studied from Pakistan. Two species, Ptecticus kerteszi De Meijere, 1924 and Ptecticus vulpianus (Enderlein, 1914) are recorded for the first time from Pakistan. The previously known Ptecticus melanurus (Walker, 1848) is reported for the first time from Poonch district, Azad Kashmir, Pakistan. The identification key to the known species along with their geographical distributions, photographs and habitats are provided.
Keywords: Ptecticus; Stratiomyidae; New Records; Azad Kashmir; Pakistan.